Accrual of Alzheimer's disease pathology as a function of proximity to parental dementia onset - Elina T. Ziukelis; Elijah Mak; Craig Ritchie; John T. O'Brien; Dag Aarsland; for the European Prevention of Alzheimer's Disease (EPAD) Consortium (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring)
Abstract INTRODUCTION Whether temporal proximity to parental onset of dementia (PPO) can be used to estimate timing of the preclinical stage of sporadic Alzheimer's disease (AD) remains uncertain. METHODS We investigated cross‐sectionally adults aged > 50 without dementia included in the European Prevention of Alzheimer's Dementia (EPAD) study. PPO was tested as a predictor of quantitative levels of cerebrospinal fluid (CSF) β‐amyloid (1‐42) (Aβ1‐42) in those with a parental history of dementia (n = 688) and of phosphorylated tau (p‐tau) and EPAD neuropsychological examination (ENE) subscores in an amyloid positive subgroup (n = 226). Possible interactions were explored. RESULTS Shorter PPO predicted lower CSF Aβ1‐42 level (β = 9.357; T = 4.161; p < 0.001), interacting with apolipoprotein E (APOE) ‐𝜀4 carriage in a dose‐dependent manner. Concomitant APOE‐𝜀2 carriage appeared to provide protection. PPO did not predict p‐tau levels or cognitive performance. DISCUSSION PPO may provide a valid method of stratifying risk of early AD pathologic change in APOE‐𝜀4 carriers, with empirical and clinical applications. Highlights Proximity to age of parental dementia onset can predict amyloid accrual The effect is APOE‐𝜀4 dose‐dependent and APOE‐𝜀2 appears to provide protection PPO does not appear to predict further advancement along the AD continuum In the era of anti‐amyloid treatments, this may inform timing of amyloid screening Used as an empirical metric, PPO could help elucidate the natural history of LOAD